2021
DOI: 10.1177/03010066211065230
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Face Masks and Viewers’ Anxiety on Ratings of First Impressions from Faces

Abstract: Face mask is now a common feature in our social environment. Although face covering reduces our ability to recognize other's face identity and facial expressions, little is known about its impact on the formation of first impressions from faces. In two online experiments, we presented unfamiliar faces displaying neutral expressions with and without face masks, and participants rated the perceived approachableness, trustworthiness, attractiveness, and dominance from each face on a 9-point scale. Their anxiety l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 49 publications
(73 reference statements)
3
18
2
Order By: Relevance
“…Even though the differential evaluation of the two types of targets varied in strength as a function of the specific dimension (i.e., being lower in the case of sociability), the effects were generally rather strong and unrelated to participants' political orientation. In sum, findings provide support to previous work attesting a bias in favor of mask wearers 14,[24][25][26][27][28] , although it should be acknowledged that the sample recruited in the present study is not necessarily representative of the whole population and therefore conclusions should be taken with caution.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Even though the differential evaluation of the two types of targets varied in strength as a function of the specific dimension (i.e., being lower in the case of sociability), the effects were generally rather strong and unrelated to participants' political orientation. In sum, findings provide support to previous work attesting a bias in favor of mask wearers 14,[24][25][26][27][28] , although it should be acknowledged that the sample recruited in the present study is not necessarily representative of the whole population and therefore conclusions should be taken with caution.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, an accurate interpersonal perception can be impoverished due to the presence of face masks.Social judgment after the emergence of Covid-19 pandemic appears to be also shaped by the presence vs. absence of face masks on the evaluation targets. Indeed, individuals wearing a face mask tend to be judged as more attractive, approachable, and trustworthy 14,[24][25][26][27][28] , although some studies failed to report similar effects 17,[29][30][31] . The positive evaluation of mask wearers found in previous research is likely to reflect the fact that mask wearing is seen as a normative behavior 32 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They argued that when a face mask partially covered a face, context cues used to predict attributes were invisible, establishing a sense of insecurity that impacts social judgments. Contrary to their research, however, several studies have reported that faces wearing face masks were perceived as more trustworthy than unoccluded faces [ 18 20 ]. Guo et al [ 18 ] argued that mask-wearers are likely to be viewed as those who are more considerate, law-binding, and rule followers, care for their own health, and are less harmful to others.…”
Section: Introductionmentioning
confidence: 85%
“…For instance, Hies and Lewis (2022) found that face masks increased ratings of attractiveness, and this was equally true for both unattractive and attractive faces. Further, when faces were considered without categorising into low and high groups, no overall differences were found when rating faces with versus without face masks (Bennetts et al, 2022;Guo et al, 2022).…”
Section: Introductionmentioning
confidence: 91%